Force Analysis of the Support Belt and Pregnant Woman for Relieving the Pregnancy-related Waist Pain (Journal of Fiber Bioengineering and Informatics, 2019)
Researching the waist support belt becomes more important. It’s said that the waist support belt canhelp pregnant women to relieve pregnancy-related pain, but the function of support belt couldn’t beunanimously identified by studies or clinical trials’ confirm at present. In this paper, the force analysismodel is established, aiming to detect the role of the waist support belt. Aiming at the dressing effect isnot prominent, when pregnant women just wear the waist support belt. In the paper, analyzing the paincauses of the pregnant women’s waist by the theory of mechanics is the basis of research. Through forceanalysis, it is effective to know how the support belt plays the role. Then, data by pressure test is usedto understand the effect, if the support belt can relieve the waist pain of pregnant women. The resultis used to verify the results of force analysis. And the data of pressure can explain its functionality. Itprovides a evaluation method of waist support belt through force analysis and pressure test.
Keywords: Force Analysis; The Support Belt; Relieve the Pregnancy-related Waist Pain; Pressure Test.